Community Archaeology at Tel Esur - Bar, Shay (The Biblical archaeology review, 2022)
At dawn, scores of schoolchildren noisily cross the wheat fields and arrive, full of enthusiasm, at the ancient mound. "Let’s find out what was here thousands of years ago!" they shout in Hebrew. The archaeologists raise their heads from sorting and registering finds—another day of community archaeology has begun at Tel Esur. Tel Esur […]